PKM KELOMPOK INDUSTRI PENGOLAHAN LIMBAH SABUT KELAPA (COCOPEAT) DI KABUPATEN DAN KOTA PROBOLINGGO PROVINSI JAWA TIMUR - Supraptiningsih, Linda; Hattarina, Shofia (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
This PKM program is aimed at productive economic communities (SMEs) in the regions of Probolinggo. The SME is owned by Mrs. Ana Aliya (Partner 1) and Mr. Agus Susanto (Partner 2). Both Partners work together to process and market coconut fiber that called cocopeat. Partner 1 is located in Wonomerto Probolinggo. Partner 2 is located in Mayangan Probolinggo. The Problems arise when partners cannot fulfill large amounts of cocopeat demand due to not yet optimal production and management processes. one problem in the production process is the length of the drying process of wet cocopeat powder that depends on sunlight. In addition, the dry cocopeat sieve process is still manual, so that it takes a relatively long time while the market demand is getting higher. Another Management problems experienced by partners are not yet optimal in the financial management system and organization. The Concrete steps done by proposers to overcome these problems include discussing with partners and collecting references, making machine designs, testing machines, carrying out financial management and organizational training. The output of this program is in the form of wet cocopeat presses, dry cocopeat sifter machines, training in financial and organizational management, counseling of waste material processing and scientific journals.